2018
DOI: 10.1016/j.ihj.2018.09.007
|View full text |Cite
|
Sign up to set email alerts
|

Correlation of the telomere length with type 2 diabetes mellitus in patients with ischemic heart disease

Abstract: ObjectiveThe study aimed to explore the relationship of the telomere length with type 2 diabetes mellitus (DM) among patients with ischemic heart disease (IHD).MethodThis 2-year cross-sectional study included 130 male patients diagnosed with IHD through echocardiography and coronary angiography, wherein consecutive IHD patients with type 2 DM (65) and without type 2 DM (65) were selected. Baseline characteristics including age, gender, body mass index, and blood pressure were recorded. Laboratory investigation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 25 publications
0
7
0
Order By: Relevance
“…Although a number of studies have shown an association between telomere length and diabetes [23,24,25,26,27,28,29,30,31] in some, this association was weak [28], cell type dependent [24] or associated with heart disease [30,31]. Sampson et al measured the telomere length of peripheral blood monocytes and T-cells in Type 2 diabetes and normal controls.…”
Section: Discussionmentioning
confidence: 99%
“…Although a number of studies have shown an association between telomere length and diabetes [23,24,25,26,27,28,29,30,31] in some, this association was weak [28], cell type dependent [24] or associated with heart disease [30,31]. Sampson et al measured the telomere length of peripheral blood monocytes and T-cells in Type 2 diabetes and normal controls.…”
Section: Discussionmentioning
confidence: 99%
“…In T2DM patients, the antiinflammatory adipokine adiponectin was found to positively correlate with TL, therefore adiponectin could potentially slow down aging 49 . Patients with ischaemic heart disease show a substantial correlation between telomere shortening and T2DM 50 . Age, known diabetes duration, blood pressure, glucose management, and baseline lipid levels were all linked with TL 51 .…”
Section: Discussionmentioning
confidence: 99%
“…Firstly, age has been shown to negatively affect TL, with older age linked to shorter telomeres (12). Secondly, smoking has also been shown to negatively affect TL and likewise, so have the comorbidities; type 2 diabetes and obesity (30)(31)(32). Thirdly, research has also shown a link between short telomeres and hypertension, chronic obstructive pulmonary disorder and coronary heart diseasethe other comorbidities included within M4 (33-35).…”
Section: Discussionmentioning
confidence: 99%